Antibacterial Activity and Stability of Polysaccharides from Meitan White Tea on Staphylococcus aureus - Shanshan SONG; Aihua YANG; Xiaomin WANG; Wan LONG; Weiwei WANG (Shipin gongye ke-ji, 2022)
Objective: To study the antibacterial activity and stability of polysaccharides from Meitan White Tea against standard strains of Staphylococcus aureus in vitro. Method: The minimum inhibitory concentration (MIC) of polysaccharides from Meitan White Tea on Staphylococcus aureus was determined by oxford cup test and microdilution broth method. The effects of temperature, pH, ultraviolet and metal ion on the antibacterial activity of polysaccharides from Meitan White Tea were studied. Results: The polysaccharides from Meitan White Tea had significant antibacterial activity against Staphylococcus aureus, and the minimum inhibitory concentration was 8 mg/mL. The bacteriostatic stability experiment of MIC was carried out, and the OD600 value of Staphylococcus aureus was used as an index. The results showed that the antibacterial activity of polysaccharides from Meitan White Tea was stable at 20~60 ℃, but it decreased slightly after being treated at high temperature (80~100 ℃), about 45.8% retained at high temperature compared with 4 ℃. The antibacterial activity remained stable at pH4~10. After 30 W ultraviolet treatment for 10~50 min, the antibacterial activity had no significant change (P>0.05). Under the treatment of 0.1 mol/L Na+ and K+, the antibacterial activity was stable, but under the treatment of 0.1 mol/L Ca2+, the antibacterial activity was lost. Conclusion: The polysaccharides from Meitan White Tea have stable inhibitory activity against Staphylococcus aureus in vitro, which provides a basis for its development as a natural preservative.